2014
DOI: 10.1098/rstb.2013.0511
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic setting and reprogramming for neural cell fate determination and differentiation

Abstract: In the mammalian brain, epigenetic mechanisms are clearly involved in the regulation of self-renewal of neural stem cells and the derivation of their descendants, i.e. neurons, astrocytes and oligodendrocytes, according to the developmental timing and the microenvironment, the 'niche'. Interestingly, local epigenetic changes occur, concomitantly with genome-wide level changes, at a set of gene promoter regions for either down-or upregulation of the gene. In addition, intergenic regions also sensitize the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 102 publications
(135 reference statements)
0
14
0
1
Order By: Relevance
“…In addition, it has been proposed that pancRNAs might bind epigenetic factors, promoting the fold of the chromatin into a transcriptionally competent ternary structure, named R-Loop and composed by the nascent RNA annealed with its complementary ssDNA and the nontemplate ssDNA. Another possibility was that pancRNAs may perhaps stabilize the active state of chromatin through the association with small dsRNAs, which in turn, could cover the catalytic site of methyl transferases [38].…”
Section: Pancrnas: Regulators Of Transcription In Developmental Procementioning
confidence: 99%
“…In addition, it has been proposed that pancRNAs might bind epigenetic factors, promoting the fold of the chromatin into a transcriptionally competent ternary structure, named R-Loop and composed by the nascent RNA annealed with its complementary ssDNA and the nontemplate ssDNA. Another possibility was that pancRNAs may perhaps stabilize the active state of chromatin through the association with small dsRNAs, which in turn, could cover the catalytic site of methyl transferases [38].…”
Section: Pancrnas: Regulators Of Transcription In Developmental Procementioning
confidence: 99%
“…There is a growing body of evidence of the importance of epigenetic regulation in behavioral and cognitive processes [71]. Epigenetic influence has been observed in brain development and neuroplasticity [2,49,50,154,163,173], neuron differentiation [86], also learning and memory formation [24,28,37,51,54,90,144], including fear memory formation [77,89,131]. Epigenetic mechanisms are also involved in aging, neurological diseases, mood and psychotic disorders, cognitive impairments or response to trauma [19,50,83,144,163,169,173].…”
Section: Epigenetic Revolutionmentioning
confidence: 99%
“…Nestin is a neural stem/progenitor cell marker (Michalczyk and Ziman, 2005). NeuN is a specific marker of postmitotic neurons (Lavezzi et al, 2013), and NEFL is abundantly found in mature neurons (Imamura et al, 2014). Synaptophysin is an integral membrane protein of small synaptic vesicles, which is present in mature terminals and outgrowing axons (Bergmann et al, 1991(Bergmann et al, , 1993Grabs et al, 1994).…”
Section: Cpf Altered the Expression Of Several Neuron-specific Genesmentioning
confidence: 99%